Direct photolysis at 184.9 nm: An underestimated pathway for organic micropollutant removal during VUV/UV treatment - Yicheng Wang; Bas A. Wols; Tomas Lock Feixas; Wolfgang Gernjak (Journal of Water Process Engineering, 2026)

Nuclear and organellar phylogenies provide insights into evolutionary history and species boundaries in Galdieria - Manuela Iovinella; Sarah C.L. Lock; Luke C.M. Mackinder; James P.J. Chong; Georg A. Feichtinger; Sally James; Daniel Jeffares; Antonino Pollio; Emanuele Del Guacchio; Hwan Su Yoon; Claudia Ciniglia; Seth J. Davis (Algal Research, 2026)

Symbiodiniaceae and Bacterial Microbiome Dynamics Differentially Impact the Survival of Dominant Reef‐Flat Porites Corals - Colin Lock; Therese C. Miller; Colin J. Anthony; Héloïse Rouzé; James Fifer; Grace McDermott; Carlos A. Tramonte; Loreto Paulino; Sarah W. Davies; Laurie Raymundo; Bastian Bentlage (Environmental Microbiology, 2025)
Coral reefs face significant threats across the globe, prompting a surge in restoration efforts aimed at mitigating their global decline. The health, resilience, and adaptability of corals are greatly influenced by their microbial communities, and while the response of coral microbiomes to many environmental stressors has been extensively studied, less is known about their natural dynamics following transplantation, which is an essential process for restoring degraded reef habitats. In this study, we integrated DNA metabarcoding (16S & ITS2) with ecological monitoring to investigate the dynamics of Symbiodiniaceae and bacterial communities in two dominant coral spp., Porites lobata and Porites cylindrica , and their different colour morphs, as they underwent transplantation and an 18‐week acclimatisation period. We saw significant differences in microbial communities between the two Porites spp., outplanting sites, and individual coral colonies, as well as a colour morph‐related difference in P. lobata bacterial communities. We saw reduced relative abundances of Endozoicomonadaceae, specifically from the genus Parendozoicomonas, following transplantation. P. lobata colonies with later Symbiodiniaceae shifts (18 weeks) had lower long‐term survival. Changes in Symbiodiniaceae and bacterial communities have implications for holobiont function and colony survival, which should be considered when designing and implementing coral reef rehabilitation projects.

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Representation of Boundary-Layer Processes in Numerical Weather Prediction and Climate Models - John M. Edwards; Anton C. M. Beljaars; Albert A. M. Holtslag; Adrian P. Lock (Boundary-Layer Meteorology, 2020)

Correction to: Defining the role of cytoskeletal components in the formation of apoptopodia and apoptotic bodies during apoptosis - Sarah Caruso; Georgia K. Atkin‑Smith; Amy A. Baxter; Rochelle Tixeira; Lanzhou Jiang; Dilara C. Ozkocak; Jascinta P. Santavanond; Mark D. Hulett; Peter Lock; Thanh Kha Phan; Ivan K. H. Poon (Apoptosis, 2019)

Defining the role of cytoskeletal components in the formation of apoptopodia and apoptotic bodies during apoptosis - Sarah Caruso; Georgia K. Atkin-Smith; Amy A. Baxter; Rochelle Tixeira; Lanzhou Jiang; Dilara C. Ozkocak; Jascinta P. Santavanond; Mark D. Hulett; Peter Lock; Thanh Kha Phan; Ivan K. H. Poon (Apoptosis, 2019)

Inter-laboratory study of human in vitro toxicogenomics-based tests as alternative methods for evaluating chemical carcinogenicity: a bioinformatics perspective - R. Herwig; H. Gmuender; R. Corvi; K. M. Bloch; A. Brandenburg; J. Castell; L. Ceelen; C. Chesne; T. Y. Doktorova; D. Jennen; P. Jennings; A. Limonciel; et al. (Archives of Toxicology, 2016)

Spatiotemporal distribution of thunderstorm initiation in the US Great Plains from 2005 to 2007 - Noah A. Lock; Adam L. Houston (International Journal of Climatology, 2015)
A first‐of‐its‐kind automated thunderstorm tracking algorithm that relies on radar reflectivity data and cloud‐to‐ground lighting is used to identify the spatiotemporal distribution of thunderstorm initiation over the central United States for 2005–2007. Nearly 56 000 thunderstorm initiations are identified. High concentrations of thunderstorm initiation are found near prominent topography and near the Gulf coast. The annual distribution exhibits a peak in August and the diurnal cycle exhibits a peak at the local solar noon with the majority of initiations occurring between 2 h prior to and 6 h past the local solar noon. While the results are largely expected, no previous study has documented the distribution of thunderstorm initiation over the geographic extent and period of record used to develop the results presented here.

Maladaptation and phenotypic mismatch in hatchery‐reared Atlantic salmon Salmo salar released in the wild - R. Stringwell; A. Lock; C. J. Stutchbury; E. Baggett; J. Taylor; P. J. Gough; C. Garcia de Leaniz (Journal of Fish Biology, 2014)
Changes in body shape, fluctuating asymmetry ( FA ) and crypsis were compared among Atlantic salmon Salmo salar fry kept as controls in captivity and those released and subsequently recaptured in the wild according to a before‐after‐control‐impact ( BACI ) design. Hatchery fish that survived in the wild became more cryptic and displayed a much lower incidence of fin erosion and of asymmetric individuals than control fish kept in captivity. Significant differences in body shape were also apparent, and survivors had longer heads, thicker caudal peduncles and a more streamlined body shape than hatchery controls as early as 20 days following stocking, most likely as a result of phenotypic plasticity and non‐random, selective mortality of maladapted phenotypes. Hatchery‐reared fish typically perform poorly in the wild and the results of this study indicate that this may be due to phenotypic mismatch, i.e. because hatcheries generate fish that are phenotypically mismatched to the natural environment.

Oxidative stress induced by potassium bromate exposure results in altered tight junction protein expression in renal proximal tubule cells - Alice Limonciel; Anja Wilmes; Lydia Aschauer; Robert Radford; Katarzyna M. Bloch; Tara McMorrow; Walter Pfaller; Joost H. van Delft; Craig Slattery; Michael P. Ryan; Edward A. Lock; Paul Jennings (Archives of Toxicology, 2012)

A comparison of the short-term toxicity of cadmium to indigenous and alien gammarid species - Pieter Boets; Koen Lock; Peter L. M. Goethals; Colin R. Janssen; Karel A. C. De Schamphelaere (Ecotoxicology, 2012)

Indirect estimates of breeding and natal philopatry in an obligate avian brood parasite - Mark E. Hauber; Bill M. Strausberger; Kevin A. Feldheim; Justin Lock; Phillip Cassey (Journal of Ornithology, 2012)

Transcriptomic alterations induced by Ochratoxin A in rat and human renal proximal tubular in vitro models and comparison to a rat in vivo model - Paul Jennings; Christina Weiland; Alice Limonciel; Katarzyna M. Bloch; Robert Radford; Lydia Aschauer; Tara McMorrow; Anja Wilmes; Walter Pfaller; Hans J. Ahr; Craig Slattery; Edward A. Lock; et al. (Archives of Toxicology, 2012)

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment - G. Svensson; A. A. M. Holtslag; V. Kumar; T. Mauritsen; G. J. Steeneveld; W. M. Angevine; E. Bazile; A. Beljaars; E. I. F. de Bruijn; A. Cheng; L. Conangla; J. Cuxart; et al. (Boundary-Layer Meteorology, 2011)

Dietary fatty acids and inflammation in the vertebral column of Atlantic salmon, Salmo salar L., smolts: a possible link to spinal deformities - L Gil Martens; E J Lock; P G Fjelldal; A Wargelius; P Araujo; B E Torstensen; P E Witten; T Hansen; R Waagbø; R Ørnsrud (Journal of Fish Diseases, 2010)
Vegetable oils (Vo) are an alternative to fish oil (Fo) in aquaculture feeds. This study aimed to evaluate the effect of dietary soybean oil (Vo diet), rich in linoleic acid, and of dietary fish oil (Fo diet) on the development of spinal deformities under bacterial lipopolysaccharide (LPS)‐induced chronic inflammation conditions in Atlantic salmon, Salmo salar L. Fish [25 g body weight (BW)] were fed the experimental diets for 99 days. On day 47 of feeding (40 g BW), fish were subjected to four experimental regimes: (i) intramuscular injections with LPS, (ii) sham‐injected phosphate‐buffered saline (PBS), (iii) intraperitoneally injected commercial oil adjuvant vaccine, or (iv) no treatment. The fish continued under a common feeding regime in sea water for 165 more days. Body weight was temporarily higher in the Vo group than in the Fo group prior to immunization and was also affected by the type of immunization. At the end of the trial, no differences were seen between the dietary groups. The overall prevalence of spinal deformities was approximately 14% at the end of the experiment. The Vo diet affected vertebral shape but did not induce spinal deformities. In groups injected with LPS and PBS, spinal deformities ranged between 21% and 38%, diet independent. Deformed vertebrae were located at or in proximity to the injection point. Assessment of inflammatory markers revealed high levels of plasma prostaglandin E 2 (PGE 2 ) in the Vo‐fed and LPS‐injected groups, suggesting an inflammatory response to LPS. Cyclooxigenase 2 (COX‐2) mRNA expression in bone was higher in fish fed Fo compared to Vo‐fed fish. Gene expression of immunoglobulin M (IgM) was up‐regulated in bone of all LPS‐injected groups irrespective of dietary oil. In conclusion, the study suggests that Vo is not a risk factor for the development of inflammation‐related spinal deformities. At the same time, we found evidence that localized injection‐related processes could trigger the development of vertebral body malformations.

Spatial representation of overlearned arbitrary visuomotor associations - Meike J. Grol; Ivan Toni; Mireille Lock; Frans A. J. Verstraten (Experimental Brain Research, 2009)

Reproduction in an invasive exotic catfish Pterygoplichthys disjunctivus in Volusia Blue Spring, Florida, U.S.A. - M. A. Gibbs; J. H. Shields; D. W. Lock; K. M. Talmadge; T. M. Farrell (Journal of Fish Biology, 2008)
Morphology and reproductive strategies of a population of invasive loricariid catfish, Pterygoplichthys disjunctivus , in Volusia Blue Spring, Florida, were examined using morphological characters, gonado‐somatic indices and batch fecundity. This species has cystovarian ovaries, a left ovary that is significantly larger than the right ovary, and is highly fecund. Ovaries contained multiple oocyte size classes and completely spent females were not found, both of which indicate that this species is a multiple spawner. Reproductive patterns changed significantly between the first (2005) and the last (2007) years of this study; female fish became capable of spawning at a smaller size, a greater proportion of the captured population were capable of spawning each year and female batch fecundity increased, as did male and female gonado‐somatic indices. Plasticity of P. disjunctivus reproductive patterns is discussed in relation to resource availability and environmental stability.

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Renal cysteine conjugate C-S lyase mediated toxicity of halogenated alkenes in primary cultures of human and rat proximal tubular cells - Trevor A. McGoldrick; Edward A. Lock; Vicente Rodilla; Gabrielle M. Hawksworth (Archives of Toxicology, 2003)

Effects of Mining Activities on Heavy Metal Concentrations in Water, Sediment, and Macroinvertebrates in Different Reaches of the Pilcomayo River, South America - A. J. P. Smolders; R. A. C. Lock; G. Van der Velde; R. I. Medina Hoyos; J. G. M. Roelofs (Archives of Environmental Contamination and Toxicology, 2003)

Water resources management in the Aral Basin: a river basin management model for the Syr Darya - S. Heaven; G. B. Koloskov; A. C. Lock; T. W. Tanton (Irrigation and Drainage, 2002)
The Aral Sea environmental crisis has been created by poor water management in the river basins of the Amu Darya and Syr Darya. Nearly all the flow is abstracted for ailing irrigation schemes in the upper and middle basins, for massive river basin transfer schemes, or is lost to evaporation and seepage from reservoirs and canals. The only solution to the crisis in the lower deltas is to allow more water to flow to them. The paper argues that the only practical approach for achieving this in the short to medium term is better water management in the upper and middle river basins, and that a more rational basis for allocating water to meet the needs of all users is urgently required. The paper describes a real‐time water resources management model for the Syr Darya river that has been designed for sustainable planning and management of the water resources to meet the needs of all riparian users. The power and limitations of such models in relation to effective management of the water resources of the Aral Basin are discussed. Copyright © 2002 John Wiley & Sons, Ltd.

The Effect of Lindane on Terrestrial Invertebrates - K. Lock, K. A. C. De Schamphelaere, C. (Archives of Environmental Contamination and Toxicology, 2002)

The effect of postnatal age on L -2-chloropropionic acid-induced cerebellar granule cell necrosis in the rat - Edward A. Lock; Andrew Gyte; Stephen Duffell; Ian Wyatt (Archives of Toxicology, 2001)

The absence of cerebellar granule cell necrosis in the mouse following L- 2-chloropropionic acid administration - Edward A. Lock; Andrew Gyte; Stephen Duffell; Ian Wyatt (Archives of Toxicology, 2000)

Neurotoxic effect of L-2-chloropropionic acid on primary cultures of rat cerebellar granule cells - Nicholas C. Sturgess; Anne Rustad; Frode Fonnum; Edward A. Lock (Archives of Toxicology, 2000)

Effects of stream size on bird community structure in coastal temperate forests of the Pacific Northwest, U.S.A. - Patricia A. Lock; Robert J. Naiman (Journal of Biogeography, 1998)
Vegetation and spring breeding bird populations associated with riparian forests on high and low order rivers of the Olympic peninsula, Washington (USA), were censussed in 1990 and 1991. The objectives were to (1) provide a baseline description of bird communities associated with unmanaged riparian forests, (2) determine whether there is a difference between bird communities along large and small rivers, and (3) identify what biophysical aspects of the fluvial corridor are most important in determining bird community structure. The approach was to link riparian bird community structure to river order and discuss relationships to vegetation, geomorphology and associated hydrologic disturbance regimes. Large rivers tended to have more deciduous vegetation than small rivers (P = 0.07) . Deciduous vegetation and patch types appeared to be linked to river size through stream valley shape and disturbance history. Bird species richness and abundance were significantly higher (P on larger rivers (67–140 m width) than on small rivers (12–21 m width) and were positively correlated with the percentage of deciduous trees present at a site. The data suggest that migrant birds, such as the black‐throated grey warbler (Dendroica nigrescens) and warbling vireo (Vireo gilvus) , require large tracts of contiguous hardwoods for successful breeding. Additionally, birds such as the Hammond's flycatcher (Empidonax hammondii) and hairy woodpecker (Picoides villosus) appear to depend on the juxtaposition of hardwoods and conifers during the breeding season. We conclude that bird communities on large rivers differ from those on small rivers and that these differences occur predictably with stream order.

The role of glutathione S-transferase- and cytochrome P450-dependent metabolism in the olfactory toxicity of methyl iodide in the rat - M. P. Chamberlain; E. A. Lock; B. A. Gaskell; C. J. Reed (Archives of Toxicology, 1998)

The nephrotoxicity and hepatotoxicity of 1,1,2,2-tetrafluoroethyl- L -cysteine in the rat - Edward A. Lock; John Ishmael (Archives of Toxicology, 1998)

l -2-Chloropropionic acid metabolism and disposition in male rats: relevance to cerebellar injury - Ian Wyatt; Michael Farnworth; Andrew J. Gyte; Edward A. Lock (Archives of Toxicology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The role of glutathione in L -2-chloropropionic acid induced cerebellar granule cell necrosis in the rat - I. Wyatt; Andrew Gyte; Michael G. Simpson; Peter S. Widdowson; Edward A. Lock (Archives of Toxicology, 1996)

Bone marrow and renal injury associated with haloalkene cysteine conjugates in calves - E. A. Lock; Yulvian Sani; Richard B. Moore; Martin B. Finkelstein; M. W. Anders; Alan A. Seawright (Archives of Toxicology, 1996)

Glutathione depletion in the liver and brain produced by 2-chloropropionic acid: relevance to cerebellar granule cell necrosis - I. Wyatt; Andrew Gyte; G. Mainwaring; Peter S. Widdowson; E. A. Lock (Archives of Toxicology, 1996)

Olfactory toxicity of methyl iodide in the rat - C. J. Reed; B. A. Gaskell; K. K. Banger; E. A. Lock (Archives of Toxicology, 1995)

Chloropropionic acid-induced alterations in glucose metabolic status: possible relevance to cerebellar granule cell necrosis - Edward A. Lock; Andrew Gyte; Peter Widdowson; Michael Simpson; Ian Wyatt (Archives of Toxicology, 1995)

Immunohistochemical localisation of six glutathione S-transferases within the nasal cavity of the rat - Kulwinder K. Banger; John R. Foster; Edward A. Lock; Celia J. Reed (Archives of Toxicology, 1994)

Effects of water-borne cadmium on the skin of the common carp (Cyprinus carpio) - Y. Iger; R. A. C. Lock; J. C. A. van der Meij; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1994)

Nephrotoxicity of 4-amino-3-S-glutathionylphenol and its modulation by metabolism or transport inhibitors - Lynn M. Fowler; John R. Foster; Edward A. Lock (Archives of Toxicology, 1994)

Effect of ascorbic acid, acivicin and probenecid on the nephrotoxicity of 4-aminophenol in the Fischer 344 rat - Lynn M. Fowler; John R. Foster; Edward A. Lock (Archives of Toxicology, 1993)

Formation of N-methyl protoporphyrin in chemically-induced protoporphyria - Y. Frater; A. Brady; E. A. Lock; F. De Matteis (Archives of Toxicology, 1993)

Inhibition of ferrochelatase and accumulation of porphyrins in mouse hepatocyte cultures exposed to porphyrinogenic chemicals - Angela M. Brady; Edward A. Lock (Archives of Toxicology, 1992)

Effect of waterborne and dietary cadmium on plasma ions of the teleostOreochromis mossambicus in relation to water calcium levels - H. B. Pratap; H. Fu; R. A. C. Lock; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1989)

Deacetylation and further metabolism of the mercapturic acid of hexachloro-1,3-butadiene by rat kidney cytosol in vitro - Iona S. Pratt; Edward A. Lock (Archives of Toxicology, 1988)

Calmodulin-mediated cadmium inhibition of phosphodiesterase activity, in vitro - Gert Flik; Jan G. J. van de Winkel; Peter Pärt; Sjoerd E. Wendelaar Bonga; Robert A. C. Lock (Archives of Toxicology, 1987)

Transport of N-acetyl-S-pentachloro-1,3-butadienylcysteine by rat renal cortex - Edward A. Lock; Jenny Odum; Patricia Ormond (Archives of Toxicology, 1986)

The acute toxic effects of hexachloro-1 : 3-butadiene on the rat kidney - Edward A. Lock; John Ishmael (Archives of Toxicology, 1979)

Sexuality in mucorales - J. D. Bu'Lock; B. E. Jones; S. A. Quarrie; D. J. Winstanley (Archives of Microbiology, 1974)